Influence of temperature, pH and naloxone on the antinociceptive activity of Channa striatus (haruan) extracts in mice - Dambisya, Yoswa M.; Lee, Tat-Leang; Sathivulu, Vijayakumar; Mat Jais, Abdul Manan (Elsevier, 1999)
We have previously shown that extracts from the snakehead fish, Channa striatus (haruan), have antinociceptive activity on their own, and enhance morphine antinociception. In furtherance of that study, we investigated the effects of temperature, pH and naloxone on the antinociceptive effects of haruan extracts in the mouse abdominal constriction test. The effects of temperature were only studied on mucus extracts since the fillet extract is prepared at high temperature under pressure. There was a general loss of inhibitory activity from 88.4% at 0 °C to 61.1% at 80-100 °C, though this was only significant at 80 °C. The effects of pH were studied on both extracts. Lowering the mucus extract pH to 6.0 (unadjusted pH 7.4) did not significantly affect its activity, while raising it to 8.0 attenuated its activity. Similarly, pH changes had no effect on the fillet extract except at pH 8.0 which produced apparently lower antinociception. Pretreatment with naloxone (4 mg/kg) had no significant effect on the inhibitory effects of either extract in the abdominal constriction test. These results suggest that the active ingredient(s) of these extracts is (are) relatively stable over a wide range of temperature and between pH 6.0 and 8.0. That would be consistent with the possibility of a glycoprotein, polypeptide or polysaccharide.